Mengintip Sistem Pendidikan di Negara Termaju di Dunia. - Zidan Fernando; Dion Dwy Saputra; Wawan Saputra (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of the education system is to educate the life of the nation and also to develop the whole human being. This report uses a descriptive qualitative method by taking notes because the source was taken by listening to the oral narrative from the GURU GEMBUL YouTube channel entitled